Keketuaan Indonesia Dalam Forum Foreign Policy Global Health Tahun 2013 - Roedyati, Joevi (Jurnal Ilmiah HUBUNGAN INTERNASIONAL, 2013)
Successful development of the health sector, will greatly affect the development and support the efforts of political, economic, social and cultural as well as the implementation of the foreign policy of a country. A state has a high quality health services to the people, will support the full development process of the country. The health sector development will also create development opportunities and other related sectors, such as the development of the pharmaceutical sector, health insurance and so on. Furthermore, the health sectors high capacity can be used as an instrument of diplomacy when negotiating or lobbying with other countries. Cuba, for example, has sent thousands of doctors around the world, including Indonesia, which in the event of natural disaster tsunami. This reflects the fact, the close connection between foreign policy with the health sector, so that the sector should be getting your full attention because it involves the national interest of a country in it.Keywords : foreign policy, development, health sector, instrument, diplomacy